Effects of pH and agar on in vitro embryo culture of orange cv. Pêra - Ribeiro, Valtemir Gonçalves; Pasqual, Moacir; Ramos, José Darlan; de Oliveira Junior, Arnaldo Freitas; Carvalho, Gladyston Rodrigues (Pesquisa Agropecuaria Brasileira, 1997)
This work had the objective of determining the effects of pH and agar interaction on in vitro orange (Citrus sinensis Osb.) embryo culture. The 0; 3.5; 7.0; 10.5 and 14.0 g/L agar concentrations were associated with MS media at 3.7; 4.7; 5.7 and 6.7 pH values, previously sterilized in autoclave. The 4.7 pH value showed higher shoot and root growth. Higher percentage of plant survival was achieved at pH 6.7 at 10.5 g/L agar concentration and a linear decrease in plant fresh weight was observed as agar concentration increased.